Electrochemical Sensors for Assessing Antioxidant Capacity of Bee Products - Peres, António M. (2018)
This chapter is focused on the application of electrochemical techniques (e.g., sensors and biosensors), as the predominant methodology, to the quantification of individual or total phenolic compounds, either in standard solutions or in real matrices (e.g., plants, fruits and beverages) and their capability for assessing antioxidant activity/capacity. Specially, the potential application to evaluate antioxidant capacity of bee-hives products (e.g., propolis, honey) is addressed. Finally, the voltammetric behavior of Portuguese monofloral honeys is discussed for the first time, taking into account the expected effects of honey color and floral origin. Also, a possible relation with the expected antioxidant capacity of honeys is discussed, considering their floral origin. Works describing the use of electrochemical detection imbibed on liquid chromatographic or capillary electrophoretic configurations among other analytical methods will not be focused in this review, although their undoubtedly potentials and proved applications.